Intravenous Oxycodone versus Intravenous Morphine in Cancer Pain: A Randomized, Open-Label, Parallel-Group, Active-Control Study - Kyung-Hee Lee; Jung-Hun Kang; Ho-Suk Oh; Moon-Ki Choi; Byoung-Yong Shim; Young-Jun Eum; Hye-Jeong Park; Jin-Hyong Kang (Pain Research and Management)
Objective. To compare efficacy and safety of intravenous continuous infusion of oxycodone with morphine in patients with cancer pain. Methods. A 5-day, randomized, open-label, exploratory study at 6 sites in the Republic of Korea. Sixty-six adults aged ≥19 years with moderate-to-severe cancer pain (Numeric Rating Scale [NRS] ≥ 4) were enrolled. The study group received intravenous (IV) oxycodone, and the comparator group received IV morphine which were titrated depending on pain intensity. The efficacy endpoint is change in average NRS score from baseline to Day 5. Other assessments included worst, current, and average pain intensity; patient satisfaction; medication dose; and adverse events. Results. Both groups achieved >50% reduction in average pain intensity: from “moderate” at baseline (oxycodone versus morphine: 6.0 ± 1.8 versus 5.9 ± 1.4) to “mild” at Day 5 (2.5 ± 1.8 versus 2.8 ± 1.6). While this reduction was similar between groups (3.5 ± 2.2 versus 3.1 ± 1.8, P value = 0.562), oxycodone achieved faster pain relief (average pain: 3.0 ± 1.6 versus 3.9 ± 1.6, P value = 0.020) on Day 2 and significant NRS reductions for worst pain on Day 2 (P value = 0.045) and current pain on Day 2 (P value = 0.035) and Day 5 (P value = 0.020) compared to morphine. Patient satisfaction, adverse events, and adverse drug reactions were similar for both groups. Conclusions. For Asian patients with cancer pain, IV oxycodone is faster acting and showed similar analgesic efficacy and safety profiles as IV morphine. This trial is registered with Clinicaltrials.gov NCT02660229.